2008
DOI: 10.1073/pnas.0802894105
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis for induced formation of the inflammatory mediator prostaglandin E 2

Abstract: Prostaglandins (PG) are bioactive lipids produced from arachidonic acid via the action of cyclooxygenases and terminal PG synthases. Microsomal prostaglandin E synthase 1 (MPGES1) constitutes an inducible glutathione-dependent integral membrane protein that catalyzes the oxidoreduction of cyclooxygenase derived PGH 2 into PGE2. MPGES1 has been implicated in a number of human diseases or pathological conditions, such as rheumatoid arthritis, fever, and pain, and is therefore regarded as a primary target for dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
205
1
3

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(210 citation statements)
references
References 34 publications
1
205
1
3
Order By: Relevance
“…A putative structure of an open conformation of the active site, with a critical Arg residue (Arg-126), was obtained through modeling against the crystal structure of human LTC4S. Hence, the mPGES-1 structure presented by Jegerschöld et al (20) agrees very well with the results of our own investigation and suggests that further mechanistic studies must take into account the consequences of protein dynamics.…”
Section: Exchange Of Gsh For Its Ethylester Is Compatible With Catalysupporting
confidence: 78%
See 1 more Smart Citation
“…A putative structure of an open conformation of the active site, with a critical Arg residue (Arg-126), was obtained through modeling against the crystal structure of human LTC4S. Hence, the mPGES-1 structure presented by Jegerschöld et al (20) agrees very well with the results of our own investigation and suggests that further mechanistic studies must take into account the consequences of protein dynamics.…”
Section: Exchange Of Gsh For Its Ethylester Is Compatible With Catalysupporting
confidence: 78%
“…During the course of these investigations, Jegerschöld et al (20) reported a structure of mPGES-1 at 3.5 Å resolution, obtained by electron crystallography. GSH was found to bind in a U-shaped conformation, and, interestingly, the authors could not find an access path for PGH 2 to the bound GSH molecule, indicating that the protein was in a closed conformation and that dynamic changes, involving helices 1 and 4, occur at the active site during binding and turnover of the lipid substrate.…”
Section: Exchange Of Gsh For Its Ethylester Is Compatible With Catalymentioning
confidence: 99%
“…The structure differs significantly from the previously reported electron crystallography structure of mPGES-1 (14). In particular, glutathione binding and coordination are different in the two structures.…”
contrasting
confidence: 51%
“…This was later confirmed by the X-ray crystal structures of FLAP (10) and LTC 4 synthase (11,12). There are also low-resolution 3D electron crystallography structures of MGST1 and mPGES-1 (13,14). However, these structures did not allow for detailed structural analysis, and concerns regarding the accuracy of the MGST1 structure have been raised (15).…”
mentioning
confidence: 77%
“…3,4 Among these factors, prostaglandin E 2 (PGE 2 ) is an essential mediator that contributes to vasodilatation, pain and fever. 5,6 Additionally, PGE 2 is also overproduced in many tumours, where it aids cancer progression by promoting angiogenesis and metastasis. 7,8 In macrophages, PGE 2 production is tightly controlled by arachidonic acid (AA) release and cyclooxygenase-2 (COX-2) expression.…”
Section: Introductionmentioning
confidence: 99%